Search for supersymmetric partners of electrons and muons in proton-proton collisions at vs=13TeV; Physics Letters B; Vol. 790 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2019, 2019)
Title screen